Variabilidade de atributos físicos e químicos para recuperação de um Argissolo Vermelho sob pastagem degradada no Cerrado - Barbieri, Rayner S. [UNESP]; Montanari, Rafael [UNESP]; Teixeira Filho, Marcelo C.M. [UNESP]; Panosso, Alan R. [UNESP]; Lima, César G.R. [UNESP] (My University, 2017)
Brazilian pastures, for the most part, have been exploited using the natural fertility of the soils leaving them at some stage of degradation. The present work had the objective of evaluating the physical and chemical attributes of the soil under degraded pasture and its nutrient and limestone needs, through statistical and geostatistical analysis. NK was the only fertilization need that presented spatial dependence in the analyzed area. The central and western regions do not have good retention capacity of water and nutrients.
Spatial variability of physical and chemical attributes for the recovery of a Red Argisol under degraded pasture in the Cerrado
Keywords: Geostatistics; Need for liming and fertilization; Urochloa brizantha